Mystical Culture and Political Apathy: Understanding its Influence on Beginner Voters at Islamic Education - Dewi Ariyanti; Jannatin Aliyah; Meicha Adheline Raihanun; Mas Adam Lukman Chaubah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
The 2024 Political Party is momentum in Indonesian democracy because it involves 55-60% of young voters. Unfortunately, there is a downward trend in political participation and indications of political apathy among young people, especially first-time voters. This research aims to determine the correlation between mystical culture and political apathy in political behavior; and the factors behind the political behavior of MAN students in Malang City. This research was conducted on MAN 1 and MAN 2 students in Malang City in March - September 2023. This research used an explanatory sequential design through quantitative analysis of multiple linear regression, with variable X1 (Mystical Culture), variable X2 (Political Apathy), and variable Y (Political Behavior) explained qualitatively and descriptively. The results of this research show that mystical culture and political apathy influence the political behavior of MAN students in Malang City significantly, namely 62.1% in the positive direction. Temporary, political apathy has a fairly large partial influence, namely 66.5%, on political behavior. The conclusion from this research are political behavior patterns of MAN students in Malang City tend to be actively criticizing the government and aiming to change conditions and the political system in Indonesia. Partai Politik 2024 menjadi momentum dalam demokrasi Indonesia karena melibatkan 55-60% pemilih muda. Sayangnya, terdapat tren penurunan partisipasi politik dan indikasi apatisme politik di kalangan anak muda, terutama pemilih pemula. Penelitian ini bertujuan untuk menentukan korelasi antara budaya mistik dan apatisme politik dalam perilaku politik serta faktor-faktor di balik perilaku politik siswa MAN di Kota Malang. Penelitian ini dilakukan pada siswa MAN 1 dan MAN 2 di Kota Malang pada bulan Maret - September 2023. Penelitian ini menggunakan desain eksplanatori sequential melalui analisis kuantitatif dengan regresi linier berganda, dengan variabel X1 (Budaya Mistik), variabel X2 (Apatisme Politik), dan variabel Y (Perilaku Politik) yang dijelaskan secara kualitatif dan deskriptif. Hasil penelitian ini menunjukkan bahwa budaya mistik dan apatisme politik secara signifikan mempengaruhi perilaku politik siswa MAN di Kota Malang, yaitu sebesar 62,1% dalam arah positif. Sementara itu, apatisme politik memiliki pengaruh parsial yang besar, yaitu 66,5%, terhadap perilaku politik. Kesimpulan dari penelitian ini adalah pola perilaku politik siswa MAN di Kota Malang cenderung aktif dalam mengkritik pemerintah dan bertujuan untuk mengubah kondisi dan sistem politik di Indonesia.